Polyphenolic Compounds from Lespedeza bicolor Protect Neuronal Cells from Oxidative Stress - Darya V. Tarbeeva; Evgeny A. Pislyagin; Ekaterina S. Menchinskaya; Dmitrii V. Berdyshev; Anatoliy I. Kalinovskiy; Valeria P. Grigorchuk; Natalia P. Mishchenko; Dmitry L. Aminin; Sergey A. Fedoreyev (MDPI AG, 2022)
Pterocarpans and related polyphenolics are known as promising neuroprotective agents. We used models of rotenone-, paraquat-, and 6-hydroxydopamine-induced neurotoxicity to study the neuroprotective activity of polyphenolic compounds from Lespedeza bicolor and their effects on mitochondrial membrane potential. We isolated 11 polyphenolic compounds: a novel coumestan lespebicoumestan A (10) and a novel stilbenoid 5'-isoprenylbicoloketon (11) as well as three previously known pterocarpans, two pterocarpens, one coumestan, one stilbenoid, and a dimeric flavonoid. Pterocarpans 3 and 6, stilbenoid 5, and dimeric flavonoid 8 significantly increased the percentage of living cells after treatment with paraquat (PQ), but only pterocarpan 6 slightly decreased the ROS level in PQ-treated cells. Pterocarpan 3 and stilbenoid 5 were shown to effectively increase mitochondrial membrane potential in PQ-treated cells. We showed that pterocarpans 2 and 3, containing a 3'-methyl-3'-isohexenylpyran ring; pterocarpens 4 and 9, with a double bond between C-6a and C-11a; and coumestan 10 significantly increased the percentage of living cells by decreasing ROS levels in 6-OHDA-treated cells, which is in accordance with their rather high activity in DPPH• and FRAP tests. Compounds 9 and 10 effectively increased the percentage of living cells after treatment with rotenone but did not significantly decrease ROS levels.